Escritoras 1840-1940. Antología - GORRITI, Juana Manuela (CEAL, 1980)
CONTENIDO : SANCHEZ, MARIQUITA; MANSO, JUANA; GUERRA, ROSA; MANSILLA, EDUARDA; FERNANDEZ, SILVIA; ANDRADE, AGUSTINA; SOTO Y CALVO, EDELINA; GONZALEZ DE NICOLAI, PASTORA; STORNI, ALFONSINA; DOMINGUEZ, MA.ALICIA; DONGHI HALPERIN, RENATA; BUNGE DE GALVEZ, DELFINA; OCAMPO, VICTORIA; VILLARINO, MA. DE; LANGE, NORAH; CALANDRELLI, SUSANA